VD_FINDINFO Décision / 2014 / 1081 vom 8. September 2014 - VD Tribunal cantonal (2014)
INFRACTIONS CONTRE LE PATRIMOINE, INTENTION, NON-LIEU | 12 CP, 138 ch. 1 CP, 139 ch. 1 CP, 146 al. 1 CP, 158 ch. 1 al. 1 CP, 158 ch. 1 al. 3 CP, 310 CPP (CH), 393 al. 1 let. a CPP (CH)